Effects of ultraviolet radiation on the microbiological, physicochemical, and sensory properties of Rangpur lime juice - Acevedo, Belén Andrea (2018)
Rangpur lime juice was subjected to ultraviolet (UV) radiation as a non-thermal technology and changes in/on quality characteristics (microbiological, physicochemical and sensorial) were determined in order to extend its shelf life. UV-C treated juice resulted in 2.33 log and 2 log reductions in aciduric microorganisms and yeast and mould count, respectively. After UV-C treatment, there were no significant changes (p > 0.05) in pH, acidity and soluble solids;however antioxidant activity and the ascorbic acid content were affected by this process. The losses in ascorbic acid were 27.5 and 42% after UV-C treatment necessary to decrease 95 and 99% of the microbial load, respectively. Based on sensory analysis results, no significant differences were detected between fresh and UV-C treated juices. UV-C treatment extended the shelf life of fresh juice to 5 days during storage at 4°C.